CFTR: cystic fibrosis and beyond - Mall, Marcus A.; Hartl, Dominik (The European respiratory journal, 2014)
Cystic fibrosis (CF) remains the most common fatal hereditary lung disease. The discovery of the cystic fibrosis transmembrane conductance regulator (CFTR) gene 25 years ago set the stage for: 1) unravelling the molecular and cellular basis of CF lung disease; 2) the generation of animal models to study in vivo pathogenesis; and 3) the development of mutation-specific therapies that are now becoming available for a subgroup of patients with CF. This article highlights major advances in our understanding of how CFTR dysfunction causes chronic mucus obstruction, neutrophilic inflammation and bacterial infection in CF airways. Furthermore, we focus on recent breakthroughs and remaining challenges of novel therapies targeting the basic CF defect, and discuss the next steps to be taken to make disease-modifying therapies available to a larger group of patients with CF, including those carrying the most common mutation ΔF508-CFTR. Finally, we will summarise emerging evidence indicating that acquired CFTR dysfunction may be implicated in the pathogenesis of chronic obstructive pulmonary disease, suggesting that lessons learned from CF may be applicable to common airway diseases associated with mucus plugging. - Tweetable abstract ERSpublications - click to tweetCFTR dysfunction causes CF and may be implicated in more common chronic obstructive lung diseases, such as COPD http://ow.ly/wplhu